An overview of elastic polymeric shape memory materials for comfort fitting. (15th December 2017) - Sun, L.; Huang, W.M.; Wang, T.X.; Chen, H.M.; Renata, C.; He, L.W.; Lv, P.; Wang, C.C.
Abstract: In this paper, we briefly review the recent progress in comfort fitting using elastic polymeric shape memory materials (SMMs). First, the required features on elastic SMMs for comfort fitting are discussed. A few types of polymeric SMMs (including some commercially available ones), which have these features, are presented. A number of prototypes made of these SMMs are used to demonstrate the feasibility to achieve the concept of comfort fitting in a one-for-all manner, i.e., one sized product to comfort fit any individuals. Graphical abstract: Highlights: Available elastic polymeric shape memory polymers at present are revealed. Potential applications in comfort fitting are demonstrated. We may utilize the shape memory effect to realize one size-for-all in a cost effective manner.